Inappropriate Intra-cervical Injection of Radiotracer for Sentinel Lymph Node Mapping in a Uterine Cervix Cancer Patient: Importance of Lymphoscintigraphy and Blue Dye Injection - Kadkhodayan, Sima (Asia Ocean J Nucl Med Biol, 2014)
Herein, we report a case of sentinel lymph node mapping in a uterine cervix cancer patient, referring to the nuclear medicine department of our institute. Lymphoscintigraphy images showed inappropriate intra-cervical injection of radiotracer. Blue dye technique was applied for sentinel lymph node mapping, using intra-cervical injection of methylene blue. Two blue/cold sentinel lymph nodes, with no pathological involvement, were intra-operatively identified, and the patient was spared pelvic lymph node dissection. The present case underscores the importance of lymphoscintigraphy imaging in sentinel lymph node mapping and demonstrates the added value of blue dye injection in selected patients. It is suggested that pre-operative lymphoscintigraphy imaging be considered as an integral part of sentinel lymph node mapping in surgical oncology. Detailed results of lymphoscintigraphy images should be provided for surgeons prior to surgery, and in case the sentinel lymph nodes are not visualized, use of blue dye for sentinel node mapping should be encouraged.